Craniofacial and Dental Developmental Defects Diagnosis and Management - Wright, J Timothy.; Wright, J Timothy. (Springer International Publishing : Imprint: Springer, 2015)
This book is intended as a reference that will provide the practitioner with a framework for establishing a diagnosis and developing a suitable treatment plan in patients presenting with a range of developmental defects of the teeth. The conditions covered include failure of tooth eruption, hypodontia, premature tooth exfoliation, defects of enamel development, and defects of dentin development, with full consideration of both syndromic and non-syndromic defects. In each case the phenotype and genotype are first described, followed by diagnostic information, including the availability of genetic testing, and treatment options. Summarizing tables are used to highlight the key diagnostic features, and helpful illustrated case presentations are included. Cleft palate is also addressed, with details on etiology, phenotypes, treatment timing and approaches, and dental management. The closing chapter provides stimulating reflections on potential future directions in the diagnosis and treatment of these disorders, encompassing changes in management related to environmental–genetic interactions, tissue engineering, and materials.